Resistance or power training to enhance lower limb muscle morphology in ambulatory children with cerebral palsy? A focused systematic review with meta-analysis - Liu, Bo; You, Jizhi; Fan, Yunxiang; Xia, Yunping; Zhang, Xiang; Zhang, Yang (Frontiers in Pediatrics, 2025)
BackgroundEarly exercise interventions targeting lower limb muscles are critical for enhancing motor development in children with cerebral palsy (CP). While both resistance training, which enhances muscular strength and endurance, and power training, which targets explosive force production and movement velocity, fall under the umbrella of strength training, this focused review synthesizes current evidence on muscle hypertrophy resulting from these two modalities in children with CP.MethodsThe Web of Science Core Collection, Scopus, and Embase were searched through March 2025. Eligible studies were randomized controlled trials assessing muscle fascicle length or proxy indicators of muscle fiber diameter following resistance or power training in children with CP. A random-effects meta-analysis was performed to calculate Cohen's d comparing strength training with regular physiotherapy.FindingsEight studies met the inclusion criteria and were systematically reviewed, with five included in the meta-analysis. These five studies reported outcomes from 80 participants in the strength training group and 73 participants in the traditional physiotherapy group. All participants were ambulatory children classified with low to mild levels on the Gross Motor Function Classification System. Resistance training significantly increased muscle fiber diameter (d = 0.82, 95% CI = 0.54–1.09), whereas power training did not (d = 0.35, 95% CI = −0.29 to 0.99). Neither training modality produced a significant increase in muscle fascicle length (resistance training: d = 0.19, 95% CI = −0.17 to 0.56; power training: d = 0.37, 95% CI = −0.27 to 1.01). Notably, one study comparing power and resistance training demonstrated a highly significant improvement in muscle fascicle length (d = 1.20, 95% CI = 0.13–2.27), which may be attributed to the high-velocity, high-load nature of concentric power training.InterpretationCurrent evidence favors resistance training to increase muscle fiber diameter in ambulatory children with CP. As individuals progress, maximal loads and repetitions should be progressively increased and complemented with explosive power training to further enhance muscle fascicle length and lower limb function. The optimal protocol for children with high levels of functional disability remains to be established.